The awakening of the dinosaurian Malaysian labour laws - Ramalingam, Chithra Latha; Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2020)
The laws relating to employment are enacted to protect the rights of workers against exploitation by their employers. Although there are many laws regulating the relationship between an employee and employer in Malaysia, the focus of this article will be on the following two sources, the Employment Act 1955 (‘the EA 1955’)1 and the Industrial Relations Act 1967 (‘the IR 1967’).2 There are many reasons as to why employment law is very important and should be taken seriously. One of the many reasons are to prevent employees from being forced to overwork by employers. The EA 1955 provides inter alia, that employees should not exceed eight hours of work a day and should only work 48 hours in a week unless overtime wages are paid. Further, employees have to be given their fair amount of holidays and leaves as stated by the law. Without the EA 1955, employees may be forced to overwork which may cause many complications such as effects therefrom on their health. Furthermore, with the Children and Young Persons (Employment) Act 1966,3 the abuse of child labour can be prevented in this country. In this Act, a person aged below 14 years is categorised as child while a person above 14 and below 16, a young person. Children and young persons are only allowed to be employed in the family businesses that involve light work and do not require the use of machines. In the absence of these restrictions, there is high possibility that they may be exposed to exploitation which may lead to corruption.